Natural Law Interpretation of the Legal Relationship between Parent and Child in European Legal Thought and Its Impact on Hungarian Family Law - Herger, Eszter Cs. (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Children’s rights were not born in the second half of the 20th century but can be traced back to biblical natural law. Biblical thought reached European legal culture in two ways: directly through the spread of Christianity and indirectly through the Jewish diaspora. Although rabbinic jurisprudence developed as group law, mostly in isolation from its environment, the influence of Christian thinkers helped to define the fundamental rights of the child that appeared centuries later in the children’s rights movement. It is also a fact that the integrative view of the biblical natural law which carries the Christian premoral goods helped to conceptualize the rights of children to the rights of parents. This tradition emphasised the responsibility of parents, with the intention of shaping adult behaviour in accordance with the normative requirements of legitimate marriage and, in contrast to other forms of cohabitation, regulating procreation, parenthood and children’s rights within this framework. However, children’s rights continued to be particularly neglected in two areas until the second half of the 20th century: the distinction between legitimate children on the basis of their gender persisted, and while the church and state gradually increased the protection of children’s rights, they systematically denied rights to nonmarital children. Therefore, after a meta-perspectival overview of the thinking about children’s rights, this paper will examine also the emancipation of legitimate female children and illegitimate children through the Hungarian example, interpreting it in the light of European intellectual currents.